2021
DOI: 10.1017/s0144686x21001501
|View full text |Cite
|
Sign up to set email alerts
|

Why older rural women in Ireland want to work: it's not all about the money

Abstract: This paper extends our understanding of employment and gendered rural ageing by examining the latent benefits of paid work for mid-life women in rural Ireland. Existing social gerontology literature deals extensively with manifest financial reasons to work, consequences of gendered pay and pension inequalities, work-related health concerns and the negative impacts to an extended working life for women. However, there is much less focus on the latent non-financial positive contributions that work provides for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Work provided them with a sense of agency, self‐efficacy, self‐worth, importance, belonging, visibility, appreciation, value, and finally, power and authority. As noted by Herbert 23 and Silver, 24 older adults without major cognitive difficulties also attributed similar value to work activities. However, these work‐associated values are especially endangered due to the sociopolitical outlook on dementia.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Work provided them with a sense of agency, self‐efficacy, self‐worth, importance, belonging, visibility, appreciation, value, and finally, power and authority. As noted by Herbert 23 and Silver, 24 older adults without major cognitive difficulties also attributed similar value to work activities. However, these work‐associated values are especially endangered due to the sociopolitical outlook on dementia.…”
Section: Discussionmentioning
confidence: 58%
“…21,22 Many studies have shown that work continues to be an essential aspect of self-identity even after retirement. For instance, Herbert 23 found that older rural women continued working because it not only allowed them to maintain financial autonomy but also provided temporal structure to their lives, a sense of purpose, personal agency, and social connectivity. Silver 24 showed that people in executive positions could perceive retirement as an unwanted change forced by social pressure because work provided them with a sense of productivity, networking opportunities, significant fulfillment, and personal satisfaction they did not want to lose.…”
Section: Introductionmentioning
confidence: 99%